On the possible geological and geophysical risks and prospects of the Chernobyl Exclusion Zone - Shestopalov, V. M. (Geofizicheskiy Zhurnal, 2016)
Scientific and engineering center of radiohydrogeogeological polygon studies of the National Academy of Sciences of Ukraine. Evidence and mechanisms of the potential influence of local depression (micro-geodynamic) zones on the NPP safety were considered. The depression forms were revealed within the Chernobyl NPP site, including location of the new safe confinement. Nature of zones and character of their influence is determined by fault structures and conjugated deep degassing processes, which cannot be detected and studied by conventional methods of engineering-exploration works during NPP siting. The assumption was made that significant and still unexplored risks for nuclear facilities are associated with probable escape of deep hydrogen through the bottom of depressions along sub-bottom channels. The approaches were proposed to studying the system of “depression with its sub-bottom channel” within the sites of Chernobyl NPP and other nuclear power plants. The prospects of searching for hydrogen accumulations as efficient energy resource were considered.